2016
DOI: 10.4081/ni.2016.6322
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain treatment: still a challenge

Abstract: Neuropathic pain (NP) is the result of a series of conditions caused by diseases or lesions to the somatosensory system. Due to the better understanding of NP pathophysiology previously unexplored therapies have been used with encouraging results. In this group, acetyl-L-carnitine, alpha-lipoic-acid, cannabinoids, clonidine, EMA401, botulinum toxin type A and new voltage-gated sodium channel blockers, can be included. Besides, changing paradigms may occur with the advent of optogenetics and a better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…According to statistics, the prevalence of NP is 5–7%, and millions of patients suffer from NP globally [ 1 ]. Long-term pain not only affects sleep quality but causes depression and mental disorder, and even suicidal tendencies, and thus severely influences quality of life [ 2 ]. However, the specific mechanism of NP is unclear, and the treatment of NP remains a thorny problem.…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics, the prevalence of NP is 5–7%, and millions of patients suffer from NP globally [ 1 ]. Long-term pain not only affects sleep quality but causes depression and mental disorder, and even suicidal tendencies, and thus severely influences quality of life [ 2 ]. However, the specific mechanism of NP is unclear, and the treatment of NP remains a thorny problem.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of neuropathic pain is challenging due to its varied etiology, symptoms and underlying mechanisms [ 1 2 ]. Uncertainty regarding the nature and exact location of the lesion, especially in non-specialist settings adds to this challenge.…”
Section: Introductionmentioning
confidence: 99%
“…We found that JMJD6 is primarily localized to neurons. Many studies have shown that spinal astrocytes are important in NPP (Gwak and Hulsebosch, 2009 ; Ikeda et al, 2012 ; Chen et al, 2014 ; Old et al, 2015 ), and miscommunication between neurons and glial cells, such as astrocytes and microglia, may also play a part in NPP (Chiang et al, 2012 ; Burke et al, 2016 ; Nascimento et al, 2016 ); however, we did not observe any significant JMJD6 localization to astrocytes or microglia. In this study, we conclude that JMJD6 does not localize to astrocytes or microglia.…”
Section: Discussionmentioning
confidence: 99%
“…A growing population worldwide are suffering symptoms of neuropathic pain (NPP), such as allodynia, hyperalgesia, or paresthesia, which are caused by lesions in the somatosensory nervous system (Treede et al, 2008 ; Geber et al, 2009 ; Haanpää et al, 2010 ). Many new therapies have been proposed, such as voltage-gated sodium or calcium channel blockers; however, there is currently a lack of effective and specific treatment options, which indicates that advancing our knowledge of the pathophysiology and the mechanisms underlying this type of pain is a priority (Chang et al, 2014 ; Schestatsky et al, 2014 ; Schug and Goddard, 2015 ; Nascimento et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%